PUBLIC FINANCING TO SUPPORT FEMALE ENTREPRENEURSHIP IN ITALY - De Rosa, Serena (Piccola Impresa / Small Business, 2025)
Purpose. The study analyzes entrepreneurship as a key element to understanding a country's economic characteristics and growth trajectory, explicitly focusing on the role of women entrepreneurs. The objective is to explore how national institutions can promote and support female entrepreneurship through financial instruments and targeted programs. Design/methodology/approach. This qualitative study analyzes financial instruments supporting female entrepreneurship in Italy from 1992 to 2024. Analyzing public funding programs highlights the alignment—or lack thereof—between institutional objectives and actual support mechanisms. A dual perspective is adopted, comparing programs exclusively dedicated to women with general initiatives that include specific provisions for female entrepreneurship, focusing on the role of Invitalia SpA. Findings. The study highlights the importance of public financial tools in supporting women entrepreneurs. The analysis of calls for proposals and regulatory provisions offers a systematic overview of existing opportunities, contributing to identifying new development possibilities for female entrepreneurship. This analysis compares exclusive programs with general programs featuring dedicated components for women. Practical and Social Implications. Practical implications include mapping financing opportunities and providing valuable recommendations for public and private entities to promote female entrepreneurship. Originality of the study. This study contributes to the literature on female entrepreneurship by combining an analysis of financing policies with an operational perspective on regulatory guidelines. Its originality lies in its in-depth analysis of the funding landscape for female entrepreneurs in Italy, spanning three decades (1992–2024). By systematically comparing public programs exclusively dedicated to women with general calls for proposals containing targeted components for female entrepreneurship, the research provides a dual perspective rarely addressed in the existing literature.